If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15n + 4 = 11n + -16 Reorder the terms: 4 + -15n = 11n + -16 Reorder the terms: 4 + -15n = -16 + 11n Solving 4 + -15n = -16 + 11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-11n' to each side of the equation. 4 + -15n + -11n = -16 + 11n + -11n Combine like terms: -15n + -11n = -26n 4 + -26n = -16 + 11n + -11n Combine like terms: 11n + -11n = 0 4 + -26n = -16 + 0 4 + -26n = -16 Add '-4' to each side of the equation. 4 + -4 + -26n = -16 + -4 Combine like terms: 4 + -4 = 0 0 + -26n = -16 + -4 -26n = -16 + -4 Combine like terms: -16 + -4 = -20 -26n = -20 Divide each side by '-26'. n = 0.7692307692 Simplifying n = 0.7692307692
| -w-z=-z | | 300X+400Y=2000 | | 32u-8-12u=22u-66 | | (9x+2)(4x^2-19x-5)=0 | | 2(8y-5)=6y | | 3a+2b=5 | | -8(-5b+7)+5b= | | 5a-b=17 | | B^2=441 | | -5(7n-6)+2n= | | x^2-30-675=0 | | 4x+5y=26 | | 27=t+8t | | 6r-2s=-2 | | x+5(x+2)=58 | | 2r+s=11 | | -10(x+5)+66=-17-17 | | (-9)-b+8b=23 | | -6p-5p=22 | | -7(x+6)+5(2x+1)= | | (-9)-b+8b=-23 | | y+2=-1+3 | | 7x+31x= | | 30n+8n= | | (15x^3-19x^2-4x)=0 | | -2y+7=6y-9 | | -33v-49v= | | j+k=14 | | ln(x)+ln(x+2)=0 | | 2j-3k=3 | | 35n-1+46= | | -x-5x=0 |